Analyzing antecedents and consequence of job crafting - Susanti Saragih; Meily Margaretha; Alando Putra Situmorang (International Journal of Management, Economics and Social Sciences (IJMESS), 2020)
The purpose of this study was to investigate the antecedents and consequence of job crafting in the context of education sector and high-power distance societies, such as Indonesia where most people seem hesitant to seize on job crafting due to their appreciation to organizational hierarchies. Specifically, we examined perceived organization support, job demand, and job autonomy as the antecedents to job crafting. Further, we tested the effect of these associations on job engagement as the consequence. According to job demand resources theory, employees voluntarily modify their job aspects (job crafting) when they perceive organization support, experience high work demand, and satisfy with the degree of autonomy. Consequently, this leads to the enhancement of employee's engagement level. To investigate these relationships, a survey was conducted among 287 early childhood and primary school teachers working in 16 schools in Bandung, West Java, Indonesia. We used path analysis to test the hypothesized models. The results indicate that perceived organization support, job demand, and job autonomy are positively associated to job crafting. In addition, we found that when job crafting is present, it increases the level of employee engagement. This study highlights the importance of job crafting for early childhood and primary school teachers working in the high-power distance societies.
Keywords: L23; 330; Job crafting; job engagement; organization support; job demand; job autonomy; primary school teacher; early childhood teacher